Gawai Dayak as an Instrument of Cultural Diplomacy and Cross-Border Acculturation between Indonesia and Malaysia - Magista Pangestu Singka (Jurnal Impresi Indonesia, 2026)
Gawai Dayak is a harvest festival of the Dayak people, celebrated in Sarawak (Malaysia) and West Kalimantan (Indonesia). Beyond its cultural significance, Gawai Dayak serves as a medium for cultural diplomacy and fosters acculturation across the Indonesia–Malaysia border. This paper examines how Gawai Dayak functions as an instrument of cross-border cultural diplomacy and social integration. To analyze the role of Gawai Dayak in bridging communities across national boundaries and promoting mutual understanding. A qualitative approach is used, including literature review of prior studies and analysis of cross-border Gawai events.  Gawai Dayak celebrations create shared identity and unity among Dayak communities of both countries, facilitating people-to-people diplomacy. The festival encourages exchange of cultural practices, language, and values, evidenced by cross-border participation in Gawai events and government-supported cultural programs. These interactions strengthen social bonds and contribute to tourism and goodwill. Gawai Dayak transcends its ritual roots to become a strategic cultural diplomacy tool, enhancing Indonesia–Malaysia relations at the grassroots level while preserving indigenous heritage. It exemplifies how shared culture can reduce inter-nation tensions and build a sense of common identity in a borderland context.